Experiences that trigger academic burnout in nursing students - Rodríguez Navarro, Jessica (2023)
Objective: To describe the experiences that trigger academic burnout in nursing students. Methods: Qualitative phenomenological study conducted from August 2022 to June 2023, in a public university in Guanajuato. Selection criteria: undergraduate nursing students from 5th to 8th semesters, between 18 and 23 years old, nursing students who completed a practicum in the hospital setting. Convenience sampling with 10 participants, considering the information saturation criterion. Data collection through a phenomenological interview with a trigger question. Phenomenological thematic analysis, the criteria of the General Health Law on Health Research were respected. Main results: Themes emerged from the analysis: 1. Meaning of exhaustion, 2. Work overload, 3. Dynamics of practices and classes, 4. Emotional charge, 5. Impact it generates in life. It has been evidenced that nursing students do develop academic burnout derived from various factors such as overload, including the modification in terms of personal dynamics that influences this burnout by combining school with other activities. Conclusion: Nursing students who have taken some practice present experiences throughout the Bachelor's degree that trigger academic burnout, in which they have felt exhausted by the dynamics of practices and classes and the excessive load of activities that they develop as a whole, where as a consequence of this has an emotional impact that modifies their life dynamics.